Asymmetric physical layer design for high-speed wireless digital communications. - Badra, R.E (IEEE Journal on selected areas in communications)
High data rates and portability are conflicting requirements in the design of reliable indoor wireless data communication systems. Asymmetric system design addresses this problem by exploiting the major differences in the availability of resources (i.e., energy, space) that exist between base stations and portable units. Such an approach seeks to concentrate most of the signal processing tasks involved in the operation of the two-way wireless link at the base station. This paper presents and discusses the implications of a set of techniques for asymmetric physical layer system design based on the use of channel precoding for forward transmission. System performance is assessed via simulations using a realistic time-varying channel model. Simplified two-way antenna diversity implemented exclusively at the base station and the key issue of automatic gain control at the receive side of the precoded link are also addressed and evaluated. Simulation results confirm that the adoption of these techniques enables reliable digital communication at a data rate of 20 Mbit/s on both links while significantly reducing the power consumption of the portable unit